Development of technology and methods for detecting metal inclusions in composite materials. (September 2020) - Kuznetsov, A
Abstract: In complex multilayer structures made from PCM, metal inclusions of small sizes (from 0.1 ÷ 0.2 to 15 mm) randomly distributed throughout the material (at depths up to 100 mm), are unacceptable for normal operation, as they can penetrate into the material structure of a finished product. This paper is aimed at developing a device that provides a small error in determining the coordinates of small-sized metal inclusions in PCM when they are detected in real conditions of production and operation. Some devices capable of detecting the content of small particles in fluids or capable of detecting metal objects in various environments are known. The disadvantages of these devices are that they can only detect magnetically active particles, or large objects–more than 3–6 mm, while the location accuracy is recorded with a big error, insufficient for the detection process of small metal inclusions in PCM–from 30 mm and higher. This determines the urgency of developing a device for detecting small metal inclusions in finished products from PCM and in the technological cycle of their production. In this paper, the basic principles of the developed device are described, a block diagram of the device is presented, including the configuration of the eddy current transducer and the main processing units of the signals coming from the transducer. As confirmation of the operation of the developed device, photos of experimental studies and their results are presented in the form of the obtained dependences of the value of metal inclusions on the depth of their occurrence, from which it can be seen that the error in determining the depth of small-sized metal inclusions by the developed device did not exceed 10% and unchanged for all small-sized metal inclusions.